Risk factors for heel pressure injury in cardiovascular intensive care unit patients. Issue 5 (3rd November 2021) - Lee, Hyeon Jeong; Han, Min Young; Hwang, Jung Hwa; Park, Kang Ju; Shin, Kyung Min; Kim, Eun Sil; Lee, Hyea Jung; Lim, Arum; Han, Eun Jin; Park, Ju Yeon; Jang, Yeon Soo
Abstract: This study analyzed the risk factors for heel pressure injury in cardiovascular intensive care unit patients with the aim of laying the groundwork for preventive nursing interventions. We conducted a retrospective case‐control study of 92 patients who were admitted to the cardiovascular surgical or medical intensive care unit of a university hospital in South Korea between January and December 2017. Of these patients, 31 and 61 were included to the heel pressure injury group and the non‐heel pressure injury group, respectively. Data on their demographic, disease‐related, and intensive care unit treatment characteristics, as well as the degree of pressure injury, were collected from the hospital's electronic medical records using a standardized form. Cardiac surgery ( P  < .001), operation time ( P  = .001), use of a mechanical ventilator ( P  < .001), use of vasoconstrictors ( P  < .001), use of sedative drugs ( P  < .001), and extracorporeal membrane oxygenation treatment ( P  < .001) were identified as significant risk factors for heel pressure injury. A total of 22 patients (71%) from the heel pressure injury group developed deep tissue injury, and 16 patients (51.6%) who received extracorporeal membrane oxygenation treatment developed heel pressure injury.